Aeroelastic effects of a simple rectangular wing-box model with varying rib orientations - Othman, M. S.; Chun, O. T.; Harmin, M. Y.; Romli, F. I. (Institute of Physics Publishing, 2016)
A simple rectangular wing-box model with varying individual rib orientations has been analysed with the interest on studying their impact on flutter and divergence instabilities. The varying rib orientations offer an alteration in bending-torsional coupling characteristics, resulting in significant effect on aeroelastic behaviour of the wing. Substantial improvement is found in comparison with the baseline and parallel ribs orientation configurations, which leads to the possibility of significant weight reduction.